2018
DOI: 10.18311/ijmds/2018/18911
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of Axis Vertebra in Subjects of Indian Origin

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(22 reference statements)
0
2
1
Order By: Relevance
“…In contrast, the results of Maqbool et al,(2016) in a study done on a Pakistani population, revealed the height of the odontoid process was 19.2 mm in females with a range of (14.1 _ 22.9mm) and 20.7 mm in males with a range of (16.0 _ 24.10 mm) (20) . Present results disagree with those of Kandziora et al,(2001) who reported it to be 20.3 ± 1.90 mm (24) . Regarding the anteroposterior diameter of the odontoid process:…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, the results of Maqbool et al,(2016) in a study done on a Pakistani population, revealed the height of the odontoid process was 19.2 mm in females with a range of (14.1 _ 22.9mm) and 20.7 mm in males with a range of (16.0 _ 24.10 mm) (20) . Present results disagree with those of Kandziora et al,(2001) who reported it to be 20.3 ± 1.90 mm (24) . Regarding the anteroposterior diameter of the odontoid process:…”
Section: Discussioncontrasting
confidence: 99%
“…It was detected in 24 male (24/39) and 15 female (15/39) patients and Type II was recorded in 73 cases (65.2%). It was depicted in 44 male (44/73) and 29 female (29/73) patients and a higher prevalence in the ≤30y age group were pyramidal while the oval type showed a higher prevalence in the >30 age group (statistically significant differences) (23)(24)(25)(26)(27) . Regarding the morphological variants of the dens: In the present study we found one variant (persistent ossiculumterminale) among the sample in contrast to Perdikakis et al (2012) in their study on a Greek population retrospectively reviewing 112 patients who found an osterminale could be identifiable (with different degrees of ossification and fusion) in 22 cases (22-26-27) .…”
Section: Sharma Et Al(2008)mentioning
confidence: 99%
“…Singla et al [9] have established that the superior facets are inclined by a mean of 69.3° in the coronal plane and the inferior facets by 42.1° in the sagittal plane. There is scant information on the missing values of the facet orientation along the other Cartesian co-ordinates [10,11]. Moreover, little emphasis if any at all, has been laid on the clinical and mechanical import of this information (more attention has been paid to the feasibility of screw trajectory within the bone) [12-19].…”
Section: Anatomical Featuresmentioning
confidence: 99%